Interprofessional Education Opportunities and Challenges for Public Health Students - Wiwik Afridah (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2023)
Interprofessional education (IPE) in communities is often underrepresented in IPE initiatives, while, in practice, the need for collaboration is high enough. Interprofessional collaborative practice is challenging, especially for public health workers because some health professional education is unprofessional. Therefore, this brief review aims to comprehensively discuss the opportunities and challenges of public health students to perform interprofessional education. Study Review and data collection had been carried out within 2015-2020. Based on our review, IPE has a positive impact on students. Many students showed positive attitudes after participating in the Interprofessional Education session. Additionally, IPE is applicable for identifying benefits, challenges, and areas for modification when implementing and developing competencies. Managing interprofessional work team training is a major challenge. The approach to overcome these challenges can be realized by public health students by applying the basic skills and soft skills of public health workers, including a graphical model of public health. The model has four main tools, and particularly in the behavioral and social sciences, and health administration and policy will be a force to overcome the barriers to implementing IPE in the community. The results of the evaluation provide insight into the experiences of students, staff, facilitators, and their self-perception of competency development. Public health students perceive positively and believe that IPE can improve communication skills, collaboration, self-efficacy, readiness for interprofessional learning, and appreciation of professional roles. However, there is still a need for training modifications and expanding student roles that can improve understanding of primary health concepts and appreciation of interprofessional collaboration. This will increase students' potential to become effective healthcare providers.